Nilai – Nilai Qur’ani dalam Budaya Dalihan Na Tolu Di Kecamatan Panyabungan: Studi Living Qur’an - Fani Sefriani; Syukri (Lembaga Pendidikan Tinggi Nahdlatul Ulama (LPT NU) PCNU Kabupaten Nganjuk, 2026)
Abstract This study aims to analyze the implementation of the values of justice and brotherhood in the Dalihan Na Tolu culture in Panyabungan District and to examine their relevance to Qur'anic values through the Living Qur'an approach. Dalihan Na Tolu is a kinship system of the Mandailing people that serves as a guideline for regulating social relations through three main elements: mora, kahanggi, and anak boru. This research employs a qualitative method with a library research design. Data were collected from the Qur'an, Ibn Kathir's Tafsir, M. Quraish Shihab's Tafsir Al-Mishbah, books, scholarly journals, and other relevant studies. The data were analyzed descriptively and analytically using the Living Qur'an approach to explore how Qur'anic values are manifested in cultural practices. The findings reveal that the value of justice in Dalihan Na Tolu is reflected in the proportional distribution of roles among mora, kahanggi, and anak boru, as well as in deliberative decision-making processes that emphasize balance between rights and obligations. Meanwhile, the value of brotherhood is manifested through extensive kinship relations, mutual cooperation, social solidarity, and collective assistance in customary activities. These values are closely aligned with Qur'anic teachings, particularly QS. Al-Mā'idah [5]:8 on justice and QS. Al-Hujurāt [49]:13 on brotherhood and ta'aruf. This study concludes that Dalihan Na Tolu represents a form of Living Qur'an as it functions as a medium for internalizing Islamic values within the social life of the Mandailing Natal community. The findings contribute to strengthening the discourse on the harmonious relationship between local culture and Islamic teachings through the integration of shared ethical values